Pengelolaan Badan Usaha Milik Desa (Bumdes) Kembang Kenanga Desa Pisang Berebus Kecamatan Gunung Toar Kabupaten Kuantan Singingi - Ariesta Ramadhani; Mayarni (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
Village development is a priority in national development, so what can be done in village development is to find the root of the problems that have been experienced by rural communities. To achieve national development goals, villages are leading government agents that can reach real target groups who want to be prosperous, in an effort to improve community welfare, namely by forming a business entity, namely Village Owned Enterprises (BUMDes). This study aims to determine the management of village-owned enterprises (BUMDes) in Kembang Kenanga, Pisang Berebus Village, Gunung Toar District, Kuantan Singingi Regency. The theory used in this research is management theory by George R. Terry in Grace 2021. This type of research is descriptive qualitative with interview, observation and documentation data collection techniques. Based on the results of the study, it can be seen that the Management of Village-Owned Enterprises (BUMDes) Kembang Kenanga, Pisang Berebus Village, Gunung Toar District, Kuantan Singingi Regency is still not running fully optimally.